HUMAN TRAFFICKING TROUGH SOCIAL MEDIA - Widarini, Dwi Ajeng; Prasasti, Rati (Universitas Prof. Dr. Moestopo (Beragama), 2013)
Human trafficking is like an iceberg phenomenon. The number that hiding under the surface is greater far beyond what we can see. Human trafficking can be happened to anybody and anytime, including our relatives and neighbors who lack of knowledge and education about the subjectThus, the need for communications campaign to disseminate the knowledge necessary to prevent the human trafficking. Therefor, this paper scrutinized the campaign to raise the awareness on human trafficking by Computer Mediated Communication especially twitter. One of the interesting fact is twittter account @FemaleNotThing with tagline she is not for sale give an education and knowledge as communication campaign on human trafficking isues.This paper objective is to describe how the perception of student in Prof.Dr.Moestopo (Beragama) University on human trafficking issues from the @FemaleNotThing account and to examined the effectiveness of communication campaign by twitter account. One of the finding shown that 75% of students (n=41) aware about human trafficking issues.The use of new media in the form of communications campaign can be an alternative for the solution to introduce and raise awareness even trigger social movement on issues of human trafficking.We recommend the use of large-scale communication campaign integrated with official agency program nationally to combat human trafficking.